Effect of trade liberalization on manufacturing sector performance in Nigeria - Olanrewaju, Afolabi Luqman (2013)
This study examined the effect of trade liberalisation on manufacturing sector performance in Nigeria using secondary data sourced from Central Bank of Nigeria (CBN) statistical bulletin and other publications. This paper extends previous few empirical studies on the issue by providing some evidence from time-series data period over 1975-2011 in the context of Nigerian economy. In this study, the dependent variables was manufacturing output growth rate. The model was tested using unit root test, Bound test, Granger causality, Vector Autoregressive (VAR) and Impulse Response Function (IRF) to analysis that dynamic relationship between manufacturing output growth rate, Manufacturing capacity utilization, inflation, Trade openness and Total domestic demand. Based on the findings, this study indicates that the Granger Causality test shows that granger cause trade openness affect capacity utilization of manufacturing sector performance, total domestic demand granger cause manufacturing output while trade openness affect total domestic demand, (all is one way causality relationship). Vector Autoregressive (VAR) and Impulse Response Function (IRF) approach shows that the country’s manufacturing sector performance growth rate is affected by the past values of the GDP. Finally this paper draws some policy implications for further studies to focus on how to improve manufacturing sector performance in Nigeria